Mortality of elderly patients with acute kidney injury undergoing continuous renal replacement therapy: is age a risk factor? - Ji Hye Kim; Sang Hun Eum; Hyoung Woo Kim; Ji Won Min; Eun Sil Koh; Eun Jeong Ko; Hyung Duk Kim; Byung Ha Chung; Seok Joon Shin; Chul Woo Yang; Hye Eun Yoon (The Korean Society of Nephrology, 2024)
Background Whether advanced age is associated with poor outcomes of elderly patients with acute kidney injury (AKI) requiring continuous renal replacement therapy (CRRT) is controversial. This study aimed to evaluate age effect and predictors for mortality in elderly AKI patients undergoing CRRT. Methods Data of 480 elderly AKI patients who underwent CRRT were retrospectively analyzed. Subjects were stratified into two groups according to age: younger-old (age, 65-74 years; n = 205) and older-old (age, ≥75 years; n = 275). Predictors for 28-day and 90-day mortality and age effects were analyzed using multivariable Cox regression analysis and propensity score matching. Results Urine output at the start of CRRT (adjusted hazard ratio [aHR], 0.99; 95% confidence interval [CI], 0.99-1.00; p = 0.04), operation (aHR, 0.53; 95% CI, 0.30-0.93; p = 0.03), and use of an intra-aortic balloon pump (aHR, 3.60; 95% CI, 1.18-10.96; p = 0.02) were predictors for 28-day mortality. Ischemic heart disease (aHR, 1.74; 95% CI, 1.02-2.98; p = 0.04) and use of a ventilator (aHR, 0.56; 95% CI, 0.36-0.89; p = 0.01) were predictors for 90-day mortality. The older-old group did not exhibit a higher risk for 28-day or 90-day mortality than the younger-old group in multivariable or propensity score-matched models. Conclusion Advanced age was not a risk factor for mortality among elderly AKI patients undergoing CRRT, suggesting that advanced age should not be considered for therapeutic decisions in critically ill elderly patients with AKI requiring CRRT.